(untitled) (Student Conference Proceedings, 2025)
In the dynamic field of software development, deadline-driven projects and the constant demand for innovation often result in an underestimated burden: cognitive load. Traditional methods, e.g., questionnaires, capture the subjectively perceived cognitive load in a time- and situation-dependent manner. However, wearable sensors could provide an objective and continuous evaluation of cognitive load in everyday work situations. Our exploratory data analysis employs a holistic approach, using recorded multi-modal physiological signals during software development-typical tasks from four participants who also filled in a NASA TLX questionnaire. Following data cleaning and a comprehensive analysis, a relation between perceived cognitive load and psychophysiological data was identified using metrics such as event-related synchronization.